Organisasi Pelajar Islam Indonesia Sulawesi Selatan 1950-1960 - Nurkasri Wulan; Darman Manda; Ahmadin Ahmadin (Phinisi Integration Review, 2022)
This study aims to provide an explanation regarding the role and activities of Indonesian Islamic student organizations in South Sulawesi 1950 – 1960. This study uses qualitative research with a historical approach, namely heuristics, source criticism, interpretation and historiography. Management of data presentation using the historical method. The results of the study show that the role of Indonesian Islamic Organizations in the regeneration system is introduced about improving the quality of knowledge to existing skills. Starting from the Basic Training level to Advanced Training, which introduces how the basic sources of knowledge are to build civilization by making community group designs about beneficial traditions in society. Meanwhile, PII's activities in South Sulawesi cover the fields of education, information and social affairs.